Eco Design, Internal Environment Management, Just in Time and Organizational Performance: Examining Moderating Role of Trust - Andhyka Tyaz Nugraha; Rizqi Wahyudi; Agung Masyad Fawzi; Sunarti Sunarti (Jurnal Manajemen Indonesia, 2022)
The prime objective of the present study is to examine the impact of Just in time production, internal environmental management, and eco-design on organizational performance. Furthermore, the moderating role of trust between internal environment management and organizational performance is examined as well. The data for the present study is collected from the customers of the textile industry through convenient sampling. The response rate was 74%. The collected data was analyzed through PLS-SEM. The findings of the study revealed that eco-design and internal environmental management significantly impact organizational performance. Whereas trust moderates positively the relationship between internal environment management and organizational performance. On the other hand, the impact of just-in-time production on organizational performance is not significant. The findings of the present study are helpful for practitioners and decision-makers of the textile industry dealing in the supply chain in developing a strategy to enhance organizational performance. Keywords— Eco-Design; Trust; Organizational Performance; Internal Environment Management; Indonesia